Pelatihan Penggunaan Canva pada Desain Kemasan Produk bagi Komunitas Kubependa Rawalumbu Bekasi - Nugroho, Fifto; Listi Prambodo , Yoga (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
Rumah singgah disabilitas mandiri (KUBEPENDA) produce a variety of household processed products such as masks, processed snacks that have been packaged properly. Currently, this community has started online marketing through the marketplace. So a good image is needed in product packaging. By held product packaging design training with the application of Canva. The method used is offline counseling in the form of providing customized materials and training on the use of the Canva application to design product packaging. After the presentation of the material, as well as conducting training and evaluation, it can be seen that this counseling is going well. From the results of the evaluation carried out by freeing participants to design product packaging that they produced themselves, it can be seen that the success of the training reached 85% of the total ties of the participants. Keywords: Canva Applications, Packaging Labels, Product Packaging Design, Packaging or Packaging, Design software